Enhancing Students’ Indonesian Language Skills through Inquiry-Based Learning at Rait Al-Yaman: A Classroom Action Research - Letti Kurniawati; Anita Dewi (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) aims to explore the effectiveness of Inquiry-Based Learning (IBL) in improving students’ skills in Indonesian Language at Rait Al-Yaman. The study focuses on enhancing students’ abilities to analyze, critically assess, and communicate effectively in Indonesian through active participation in inquiry-driven tasks. The research was conducted with a group of 6th-grade students, utilizing IBL to encourage curiosity, self-directed learning, and deeper engagement with the subject matter. The objective of this study was to evaluate how IBL could foster critical thinking and improve language proficiency by having students explore real-world issues and create solutions collaboratively. The research was implemented in two cycles, each consisting of four stages: planning, action, observation, and reflection. In each cycle, students were given inquiry-driven tasks that encouraged them to explore Indonesian language concepts, such as grammar, writing, and reading comprehension, through group discussions, projects, and problem-solving activities. Data was collected through pre- and post-tests, classroom observations, and student feedback to assess the impact of IBL on students’ language skills and engagement. The findings indicate that the IBL model significantly improved students’ Indonesian language skills, as well as their ability to work collaboratively and think critically. Students demonstrated enhanced language proficiency, including better writing and reading comprehension, and increased participation in classroom discussions. This research highlights the potential of Inquiry-Based Learning as an effective method for enhancing language education by fostering a more interactive and engaging learning environment.